1997
DOI: 10.1002/stem.150334
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gene (drad‐1) Expressed in Hematopoiesis‐Supporting Stromal Cell Lines, ST2, PA6 and A54 Preadipocytes: Use of mRNA Differential Display

Abstract: We established a differentiation-inducible preadipocyte cell line, designated A54 preadipocytes, from C3H10T1/2 (10T1/2) mouse embryo fibroblasts. A54 preadipocytes had marked hematopoiesis-supporting ability in vitro but this ability was lost after terminal differentiation to adipocytes. In this study, to identify molecules that contribute to the hematopoiesis-supporting ability of A54 preadipocytes, we screened genes that were differentially expressed in A54 preadipocytes and isolated seven novel genes by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Previous studies have shown that preadipocytes have a higher ability to support hematopoiesis than other kinds of stromal cell components in vitro [12,13]. Our results of gene expression profile revealed up-regulation of critical cytokines for hematopoiesis such as SCF and SDF-1 in preadipocyte A54 cells.…”
Section: Microarray Analysis Of Genes Responsible For Differentiationsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous studies have shown that preadipocytes have a higher ability to support hematopoiesis than other kinds of stromal cell components in vitro [12,13]. Our results of gene expression profile revealed up-regulation of critical cytokines for hematopoiesis such as SCF and SDF-1 in preadipocyte A54 cells.…”
Section: Microarray Analysis Of Genes Responsible For Differentiationsupporting
confidence: 51%
“…In preadipocyte A54 cells, 201 genes were up-regulated, including genes known to be involved in adipocyte differentiation such as genes encoding C/EBPa, C/EBPd, PPAR-g, PAI-I, and Frizzled-1 [10]. Myoblasts M1601 cells showed 137 upregulated genes, including ones related to skeletal muscle differentiation such as genes encoding MyoD, MLC1F, askeletal actin, myosin heavy chain, and myosin light chain [11] as well as genes related to cardiac muscle differentiation such as genes encoding a-cardiac actin, cardiac troponin C, and troponin T2 [12].…”
Section: Microarray Analysis Of Genes Responsible For Differentiationmentioning
confidence: 99%
“…We used the mouse-derived cell lines, OP9 and C3H10T1/2, as feeder cells. Both OP9 [1015] and C3H10T1/2 [10, 16–18] have been used in many studies to maintain in vitro hematopoiesis. As we show below, both OP9 and C3H10T1/2 cells supported long-lasting in vitro hematopoiesis from human hematopoietic stem cells.…”
Section: Resultsmentioning
confidence: 99%